3 Phase Inverter Switching Algorithm for Industrial Needs. Issue 1 (February 2021) - Syafruddin, R; Nataliana, D; Hidayat, R; Anung,; Mahardika, A G; Ramady, G D
Abstract: 3 phase inverter is needed, besides to change the dc to ac voltage as needed, in the industry every CNC or NC machine needs an inverter to regulate the rotation speed of the motor, constant motor rotation requires for cutting in certain a variety of speeds feeding processes, wherein conventional machines gear is used to change the rotation speed of the motor, here the AC voltage is changed to DC and returned to AC according to the required frequency. For this reason, the researchers tried to research switching the 3 phase inverter algorithm with the principle of space vector pulse wide modulation. Here the switching theory follows the SVPWM switching rule, where the resultant vector is the result of each sector of each phase. The microcontroller accepts the input data, that will be used to generate frequency, the required PWM calculation, the sector, estimates the switching process per sector, the switching sector according to the algorithm results rule. These results will generate inter-phase voltage greater than conventional switching methods, reducing noise, switching steps shorter only 6 steps, improve the power factor. The switching algorithm is ready to be used to make 3 phase inverters.